Cognitive-behavioral stress management relieves anxiety, depression, and post-traumatic stress disorder in parents of pediatric acute myeloid leukemia patients: a randomized, controlled study - Li Wang; Hui Duan; Hongmei Zuo; Zhongyu Wang; Shuili Jiao; Yanli Liu; Huihui Li; Jie Chen (Hematology)
Objectives Cognitive-behavioral stress management (CBSM) is an effective psychological intervention to relieve psychological and symptomatic distress. This study aimed to investigate the effect of CBSM in anxiety, depression, and post-traumatic stress disorder (PTSD) in parents of pediatric acute myeloid leukemia (AML) patients.Methods Totally, 56 pediatric AML patients and 100 parents were randomized into the CBSM group (28 patients and 49 parents) and the normal control (NC) group (28 patients and 51 parents) to receive corresponding interventions for 10 weeks. The questionnaire scores were assessed at month M0, M1, M3, and M6.Results In parents of pediatric AML patients, self-rating anxiety scale score at M1 (p = 0.034), M3 (p = 0.010), and M6 (p = 0.003), as well as anxiety at M3 (p = 0.036) and M6 (p = 0.012) were decreased in the CBSM group versus the NC group. Self-rating depression scale score at M3 (p = 0.022) and M6 (p = 0.002), as well as depression at M6 (p = 0.019) were declined in the CBSM group versus the NC group. Symptom checklist-90 (a psychotic status questionnaire) score at M3 (p = 0.031) and M6 (p = 0.019) were declined in the CBSM group versus the NC group. Regarding PTSD, the impact of the events scale-revised score at M3 (p = 0.044) and M6 (p = 0.010) were decreased in the CBSM group versus the NC group. By subgroup analyses CBSM (versus NC) improved all outcomes in parents with anxiety at M0 and depression at M0 (all p < 0.050), but could not affect the outcomes in parents without anxiety or depression at M0 (all p > 0.050).Conclusion CBSM reduces anxiety, depression, and PTSD in parents of pediatric AML patients.